Esports Physical Exercise/PerformanceMatrix 1.0 Country Factsheets: a protocol for national, regional, and global annual assessment - Bo Long; Agudamu; Radenko M. Matic; Radenko M. Matic; Stevo Popovic; Stevo Popovic; Stevo Popovic; Te Bu (Frontiers in Public Health)
This protocol helps evaluators gather current data and prepare annual assessments based on specific indicators to provide insights into physical activity among esports players and identify the challenges they face. This manuscript aims to develop a methodology for creating a standardized monitoring system to assess physical exercise and performance in esports players at national, regional, and global levels. This study protocol proposes 20 online sociodemographic indicators to help characterize participating countries and outline each country’s demographic profile. Additionally, this protocol proposes nine content indicators specifically designed to assess physical exercise and performance in esports players. A separate analysis will be required to evaluate each content indicator using a 10-point grading scale. This study protocol will facilitate the annual meetings of national evaluators (researchers) to produce reports, thereby fostering effective and dynamic linkages between research and practice.